MORPHOMETRIC CHARACTERISTICS OF THE SCIATIC NERVE TRUNK IN THE ACUTE ASEPTIC INFLAMMATION IN RATS - Svyrydiuk, R.V.; Shepitko, K.V.; Shepitko, V.I.; Raskalei, T.Ya. (World of Medicine and Biology, 2018)
The total of 55 mature male rats were involved into study. The dynamics of changes in morphometric parameters in single intraperitoneal administration of 5 mg λ- carrageenan (Sigma-USA) in 1ml saline per one animal, inducing changes in the investigated morphometric indices, has been shown. Thus, the indices of the common wall, epineurium, perineurium and endoneurium of the rat sciatic nerve trunk responded to the increase of the parameter maximally on day 14 – 21 of the experiment and did not reach the indices of the intact group on day 30, indicating the manifestations of dystrophic processes with atrophy in the trunk of the sciatic nerve.
Keywords: trunk; sciatic nerve; λ- carrageenan; aseptic inflammation